THE INFLUENCE OF TRUST AND QUALITY OF INFORMATION ON PURCHASING DECISIONS THROUGH TITIP SERVICES AT J&T EXPRESS INDRAPURA: PENGARUH KEPERCAYAAN DAN KUALITAS INFORMASI TERHADAP KEPUTUSAN PEMBELIAN MELALUI JASA TITIP DI J&T EXPRESS INDRAPURA - Syahputra, M Rifaldi (LPPM UPMI, 2023)
Purchasing decision is a process in which consumers recognize the problem, seek information about a particular product or brand and properly evaluate each of these alternatives to solve the problem, which then leads to purchasing decisions. This study aims to determine how much influence trust and quality of information have on purchasing decisions at J&T Express indrapura either partially or simultaneously. The research method used is a survey method with a quantitative approach, with a population of 30 respondents. The data collection technique used was a questionnaire. The research results show that 1). There is a positive and significant influence between trust and purchasing decisions. This is shown from the results of the tcount test of 2.359 with a significance of 0.002, 2). There is a positive and significant influence between the quality of information on purchasing decisions. This is shown from the results of the t-count test of 2.680 with a significance of 0.001, 3). There is a significant influence between trust and quality of information on purchasing decisions. This is shown from the results of the calculated F test of 3.460 with a significance of 0.005, 4). Based on this study, the trust and quality of information can explain the factors that influence purchasing decisions by 30.2% and the remaining 69.8% are influenced by variables outside the research.